Digital Marketing Application for Balinese Culinary Tourism in Denpasar City - Gilang Ramadan; I Ketut Budarma; I Gede Mudana (International Journal of Glocal Tourism, 2021)
Abstract : Purpose: This research is to analyze the application of digital marketing of Balinese culinary tourism in Denpasar City, Indonesia, based on Geographic Information System. Research methods: The data collection is collected by examining and/or exploring several journals, books, and documents as well as sources of data and or other information deemed relevant to the research. Findings: The outcome of this research is a digital marketing system design of Balinese culinary tourism in Denpasar City based on the Geographic Information System. The design is to improve the marketing of Balinese culinary tourism in the city. Implications: The digital marketing model can make the users (tourists/excursionists) easier to search in mapping the location of restaurants or culinary tourism in Denpasar City quickly and precisely and can be accessed by anyone, anytime, and anywhere.